(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: STEM education, an acronym for Science, Technology, Engineering, and Mathematics, emphasizes experiential learning through the integration of these subjects. It employs hands-on activities using specially designed kits, toys, or unconventional settings to foster a practical understanding of STEM concepts. This student-centered approach positions students at the forefront of learning, while teachers act as facilitators. The implementation of Atal Tinkering Labs (ATLs) in classrooms aims to create a stimulating environment, making education more engaging and supportive of innovation. Despite its potential, this pedagogy challenges the traditional education system, necessitating curriculum and teacher education reforms. Enhancing the STEM workforce is critical for addressing global competition and improving STEM literacy. While STEM education is globally recognized and adopted, including in countries like Australia, China, and the United Kingdom, India’s efforts, particularly through ATLs, are noteworthy. This paper explores the strategies employed by India to promote STEM education, focusing on the Atal Tinkering Labs initiative, and examines its effectiveness and challenges.